A experiência do envelhecimento de mulheres em tratamento antirretroviral para HIV-AIDS. - Argolo Júnior, Cecilio (2022)
This thesis had the general aim of systemically understanding, based on the Bioecological Theory of Human Development, the experience of elder women on antiretroviral therapy (ART) for HIV/AIDS. And as specific objectives, it proposed to describe the biosociodemographic data of the old participants; identify the reactions to the HIV/AIDS diagnosis on the part of the seropositive older woman and her family from the perspective of this patient; investigate the forms of support received at that time; analyze the consequences of the diagnosis of HIV/AIDS for the older woman and her family; describe the importance of adherence to treatment; and assess the relationship between aging and the indicated treatment for HIV/AIDS. This was an observational, cross-sectional, descriptive and qualitative study. Ten older women, aged between 60 and 69 years old, seropositive, and undergoing antiretroviral treatment for HIV/AIDS participated in this research. For the data collection, two instruments were used, a biosociodemographic questionnaire, and an interview script, conducted in a semi-structured way, containing questions related to the aims of the study. For the analysis of the results, the Thematic content analysis was used in three stages, 1) pre-analysis; 2) choice of documents; 3) treatment of results. The results showed fear of death as the main reaction to the diagnosis of HIV/AIDS, followed massively by the mechanism of denial of the disease. Regarding the reaction of family members, especially of the children, sadness, surprise, and hatred towards the father were the most evident feelings in the research due to the transmission of the virus to the mother. As for the support received, in addition to the one from the family, it came from the doctors and technicians in the care unit they attend, as well as the faith they profess. The consequences of living with the virus were felt in their physical state as they incorporated panic due to the fear of the appearance of opportunistic infections linked to AIDS, being in constant vigilance not to get ill, restricting social life, confined in the face of isolation imposed by the vulnerabilities brought by the serological status itself, in the loss of work and independence, as well as in the low quality of life in general. All of them adhered to the treatment and are under constant monitoring. In conclusion, this research made it possible to know the true reality of the aging of women with HIV/AIDS on ART, many of them, poor in the form of the law, invisible to the eyes of the public power, living on the margins of society, with little information about their sexuality and total lack of knowledge about the ways of contagion of sexually transmitted infections, making them thus vulnerable to these. In view of all this, it is expected to give greater social visibility to the issue of aging women with HIV and on ART, as well as to stimulate the creation of public health, prevention and treatment policies aimed at this group of vulnerable and invisible people to the State and, still, to provide theoretical and practical subsidies to the professionals who work with this population.